A Nomogram for the Determination of the Necessity of Concurrent Chemotherapy in Patients With Stage II–IVa Nasopharyngeal Carcinoma - Yang, Kaixuan; Zhang, Qian; Zhang, Mengxi; Xie, Wenji; Li, Mei; Zeng, Lei; Wang, Qiang; Zhao, Jianling; Li, Yiping; Li, Guangjun (Frontiers in Oncology, 2021)
Background: The efficiency of concurrent chemotherapy (CC) remains controversial for stage II-IVa nasopharyngeal carcinoma (NPC) patients treated with induction chemotherapy (IC) followed by intensity-modulated radiotherapy (IMRT). Therefore, we aimed to propose a nomogram to identify patients who would benefit from CC. Methods: 434 NPC patients (stage II-IVa) treated with induction chemotherapy (IC) followed by intensity-modulated radiotherapy (IMRT) between January 2010 and December 2015 were included. 808 dosimetric parameters were extracted by the in-house script for each patient. A dosimetric signature was developed with the least absolute shrinkage and selection operator algorithm. A nomogram was built by incorporating clinical factors and dosimetric signature using Cox regression to predict recurrence-free survival (RFS). The C-index was used to evaluate the performance of nomogram. Patients were stratified into low- and high-risk recurrence according to the optimal cutoff of risk score. Results: The nomogram incorporating age, TNM stage, and dosimetric signature yielded a C-index of 0.719 (95% confidence interval [CI], 0.658-0.78). In the low-risk group, CC was associated with a 9.4% increase of 5-year locoregional RFS, and an 8.8% increase of 5-year OS, whereas it was not significantly associated with an improvement of LRFS and OS in high-risk group. However, in the high-risk group, patients could benefit from adjuvant chemotherapy (AC) by improving 33.6% of 5-year LRFS. Conclusions: The nomogram performed individualized risk quantification of RFS in patients with stage II-IVa NPC treated with IC followed by IMRT. Patients with low-risk could benefit from CC, whereas patients with high-risk may require additional AC.